Reactions to infidelity: Gender differences and relative mate value. - Phillips, April. (My University, 2005)
Two studies examined the influence of gender and mate value on responses to infidelity from an evolutionary perspective. Couples were recruited for Study 1, allowing an examination of participants' self-perceived mate value relative to their partners' mate value (relative mate value). As predicted, males responded more negatively (i.e., they reported greater levels of indignation, a greater likelihood of relationship dissolution, less forgiveness) in response to sexual infidelity compared to emotional. In addition, higher levels of relative mate value were associated with greater levels of indignation in response to infidelity, regardless of the type of affair. In Study 2, participants who had been the victim of infidelity in the past recounted their experiences and reported how they actually responded. Although evidence for gender differences in this study were weak, consistent with Study 1, higher levels of relative mate value were associated with greater levels of indignation in response to infidelity. Taken together, these two studies provide compelling support for the hypothesis that an individual's perceived relative mate value is an important predictor of reactions to infidelity (particularly levels of indignation). Although these results did not support the existence of a fundamental difference between males and females in response to sexual versus emotional infidelity, Study 1 provided compelling evidence that, at least for males, type of affair is an important predictor of reactions to infidelity.
Keywords: Adultery Psychological aspects.; Psychology, Social.